Chinese females׳ date refusals in reality TV shows: Expressing involvement or independence?. (September 2016) - Ren, Wei; Woodfield, Helen
Abstract: The majority of pragmatics research on the speech act of refusals has employed production questionnaires or role-plays to elicit data. Research employing more naturalistic data is needed to explore the actual performance of refusals, particularly in those socially sensitive contexts such as date refusals and within a public domain such as the reality TV show. The present study investigates the under-researched topic of date refusals on reality TV shows in China. The corpus in the present study comprised 38 female date refusals collected from a popular Chinese TV dating programme over a year. It was found that when refusing a date invitation in the TV show, Chinese females employed a limited range of pragmatic strategies. Their date refusals were mostly realized by means of apologies, and reasons, and to a lesser degree through adjuncts to refusals (including positive comments and gratitude) and direct refusal strategies. In addition, the Chinese females demonstrated a preference for strategies of involvement politeness in their date refusals. The paper also discusses the possible impact of the genre of reality TV shows on the Chinese females date refusals. Highlights: The paper investigated Chinese females׳ date refusals in reality TV shows. Chinese females demonstrated a preference for strategies of involvement face in their date refusals. The Chinese females employed a limited range of pragmatic strategies in their date refusals. The study contributes to the existing literature on Chinese refusals and gendered language.